Proteomics of dark cutting longissimus thoracis muscle from heifer and steer carcasses. (March 2018) - Mahmood, Shahid; Turchinsky, Nancy; Paradis, Francois; Dixon, Walter T.; Bruce, Heather L.
Abstract: Studies have suggested that the phenomenon of dark cutting (Canada B4) beef may also be related to muscle glycolytic proteins. The objective of this study, therefore, was to analyze longissimus thoracis (LT; n  = 23), from Canada AA ( n  = 8), atypical (AB4; pH < 5.9, n  = 8) and typical (TB4; pH > 5.9, n  = 7) B4 heifer and steer carcasses, for sarcoplasmic and myofibrillar proteins using 2-D gel electrophoresis and LC-MS/MS mass spectrometry. Results indicated that AB4 LT had intramuscular pH and lactate concentration similar to Canada AA but lower ( P  < 0.05) L* and b* . Moreover, AB4 LT were tougher than Canada AA even at 21 days post-mortem, unlike TB4. Canada AB4 LT had reduced ( P  < 0.05) levels of creatine kinase, glyceraldehyde-3-phosphate dehydrogenase, lactate dehydrogenase and glycerol-3-phosphate dehydrogenase [NAD(+)], indicating a compromised glycolytic capacity in AB4. Canada AB4 LT had increased ( P  < 0.05) abundances of phosphatidylethanolamine-binding protein 1 and small heat shock proteins. Highlights: Atypical dark cutting beef had reduced L* and b* value despite low ultimate pH. Atypical dark cutting beef appeared to have compromised glycolytic capacity. Phosphatidylethanolamine-binding protein 1 may contribute to the toughness of beef.